A inclusão da pessoa com deficiência e a formação inicial em línguas: uma investigação dos projetos pedagógicos de cursos de letras - Rezende, Mirelle Gonçalves de (2025)
This research is based on my personal experience as a Person with Disabilities (PWD), emphasizing that, although teacher training is essential in the sense of preparing teachers to work with students with disabilities, it must be accompanied by a collaborative commitment between society, the government and educational institutions to make educational inclusion effective. The concern that resulted in this research is due to my condition as a PWD. Although I do not work as a teacher, neither in primary education nor in higher education, I recognize the significant influence of initial teacher education on the teaching work of supporting students with disabilities. I have experienced excluding practices, as a Person with Physical Disabilities (PWD), and I realize that teacher education, at the base, to work with a wide diversity of students can contribute to a transformation of these excluding practices through education. The development of this research aims to contribute to a reflection on the initial education of language teachers and compliance with national legislation that guarantees “Education for All”, especially for the target audience of special education. This documentary research aims to analyze how the pedagogical projects of the Language and Literature courses at a federal university in Minas Gerais - the Federal University of Uberlândia (UFU) - address the inclusion of people with disabilities and accessibility. The study showed that the presence of terms such as “inclusion”, “accessibility” and “disability” in the program syllabus, although relevant, does not guarantee a deep and consistent approach. Often, these concepts appear in a fragmented way, without a practical articulation that indicates how pre-service teachers can develop skills to work in different school contexts. Inclusion is not limited to the adoption of normative discourses; it requires critical reflection and an institutional commitment to practices that go beyond the barriers of formalism and effectively promote educational equity.